Development of Morottal Media to Improve Memorization of Students MI Nurul Huda II East Bancek Pasean Pamekasan - Faridatul Jannah; Nurul Zainab (STIT Attaqwa, 2024)
This research aims to develop moral media to improve student memorization at MI Nurul Huda II East Bank Pasean Pamekasan. The method used in this research is development research by following the following methods. a). define and conduct interviews with teachers and school principals. b). design moral media. c). develop through trials so that the product is suitable for use, this validation takes the form of language validation, material validation, and media. This looks at the feasibility of developing media created by researchers, based on the validation results used by researchers to develop moral media, it is stated that it is quite good to do and apply at the MI Nurul Huda II school, East Bancek Pamekasan.